Influence of Leadership and Discipline on Satisfaction and Motivation and its The Impact On Employee Performance Social Service Manpower and Transmigration Ngawi - Sukoco, Sukoco (-)
This study aims to identify and test empirically Influence of Leadership and Discipline on Satisfaction and Motivation and its The Impact of Employee Performance Social Service Manpower and Transmigration Ngawi. The data analysis technique used is path analysis (path analysis), which will be tested by t test, F test and R2, Correlations, direct effect and the indirect effect and the total effect. The technique of collecting data using questionnaires, the sample used is an employee of Social Service Manpower and Transmigration Ngawi totaling 84 employees. T test results can be concluded that the variable Disciplinary positive and significant impact on satisfaction, leadership and positive effect not significant to satisfaction, variable Disciplinary positive and significant impact on Motivation and Leadership positive effect and no significant effect on motivation, discipline, Satisfaction and Motivation positive effect and Significantly to Performance, Leadership While no significant positive effect on performance. F test showed that all variables simultaneously positive and significant influence on employee performance. R2 test results showed that the total value of the R Square of 0.946 means that the independent variables affect the performance of 94.6%, while the remaining 5.4% is influenced by other variables outside the research model. The direct effect of leadership variable is greater than the indirect effect through the satisfaction and motivation. The direct effect of discipline variable is greater than the indirect effect through the satisfaction and motivation. Use of satisfaction and motivation as an intervening variable for increased performance, the variables of leadership, discipline is ineffective.Keywords: Leadership, Discipline, Satisfaction, Motivation, Performance